Isolated septum pellucidum agenesis in an adult - Cihangirogiu, M; Bulut, S; Yilmaz, S (Sage Publications Inc, 2002)
Septum pellucidum agenesis is frequently associated with other cerebral malformations. Its isolated agenesis is quite rare. In the literature, all reported cases were diagnosed in early childhood. The authors present an unusual case of isolated septum pellucidum agenesis detected in adulthood with computed tomography and magnetic resonance imaging.
Keywords: septum pellucidum; agenesis; magnetic resonance imaging